Volutellonectria (Ascomycota, Fungi), a new genus with Volutella anamorphs - Luo, Jing; Zhuang, Wen-Ying (Phytotaxa, 2012)
A new genus, Volutellonectria with Volutella anamorphs is established, based on and typified by Cosmospora consors. It is characterized by small, red perithecia which may collapse laterally when dry, a Cosmospora-like perithecial wall structure, clavate asci with an apical ring, fusiform ascospores with smooth surface, and growing on decaying plant debris or woody substrates. Two new species are added to the new genus and described as Volutellonectria asiana and V. ciliata. Phylogenetic analyses of nuclear ribosomal DNA (ITS and 28S partial) strongly support the separation of Volutellonectria from Cosmospora and some other species with Volutella anamorphs in Nectriaceae, as well as recognition of the new species.